Mental Health Recovery: Evaluation of a Recovery-Oriented Training Program. (23rd December 2012) - Wilrycx, G. K. M. L.; Croon, M. A.; van den Broek, A. H. S.; van Nieuwenhuizen, Ch.
Abstract : Aim . This study investigates the effectiveness of a recovery-oriented training program on knowledge and attitudes of mental health care professionals towards recovery of people with serious mental illness. Methods . Using data from a longitudinal study of recovery, changes in knowledge and attitudes of 210 mental health care professionals towards recovery were explored using the Recovery Attitude Questionnaire and the Recovery Knowledge Inventory. The study uses a two-group multiple intervention interrupted time-series design which is a variant of the stepped-wedge trial design. A total of six measurements occasions took place. Results . This study shows that professionals' attitudes towards recovery from mental illness can improve with training. After two intensive recovery-oriented training sessions, mental health care professionals have a more positive attitude towards recovery in clinical practice. Conclusion . A recovery-oriented training program can change attitudes of mental health care professionals towards recovery of serious mental illness.